2001
DOI: 10.1002/dmrr.226
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of insulin resistance and carotid intimal medial thickness in non‐diabetic Asian Indian subjects

Abstract: In southern Indians, IGT did not influence the IMT. Although insulin resistance was higher in IGT, it was not associated with higher IMT. Conventional risk factors such as cholesterol, LDL-cholesterol and apolipoproteins showed association with IMT in the insulin-resistant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…11 The finding of no association between ECAS and the apoB/apoAI ratio in this study contrasts with findings of other studies in which an increased apoB/apoAI ratio was associated with a progression in the intima-media thickness and in higher intima-media thickness values of extracranial carotid arteries. 10,20,21 This discrepancy might be attributed to ethnic differences, and, so, our findings need to be replicated in subsequent studies. One study demonstrated an ethnic difference in the association of MetS between ICAS and ECAS.…”
Section: Discussionmentioning
confidence: 72%
“…11 The finding of no association between ECAS and the apoB/apoAI ratio in this study contrasts with findings of other studies in which an increased apoB/apoAI ratio was associated with a progression in the intima-media thickness and in higher intima-media thickness values of extracranial carotid arteries. 10,20,21 This discrepancy might be attributed to ethnic differences, and, so, our findings need to be replicated in subsequent studies. One study demonstrated an ethnic difference in the association of MetS between ICAS and ECAS.…”
Section: Discussionmentioning
confidence: 72%
“…There have been several previous reports in which the association between carotid intima-media thickness and insulin resistance has been investigated in a nondiabetic population. Some studies showed a lack of independent association between insulin resistance and carotid arteriosclerosis, 9,22,23 whereas others showed a positive association between these variables. 24 Snehalatha et al 22 reported lack of an association between insulin resistance and carotid intima-media thickness in nondiabetic Asian subjects.…”
Section: Ishizaka Et Al Insulin Resistance and Atherosclerosis 297mentioning
confidence: 99%
“…Some studies showed a lack of independent association between insulin resistance and carotid arteriosclerosis, 9,22,23 whereas others showed a positive association between these variables. 24 Snehalatha et al 22 reported lack of an association between insulin resistance and carotid intima-media thickness in nondiabetic Asian subjects. Bonora et al 23 reported that carotid intima-media thickness was associated with insulin resistance in nondiabetic subjects, as determined by univariate analysis, but was not associated by multivariate analysis, although their number of enrolled subjects (nϭ58) was relatively small.…”
Section: Ishizaka Et Al Insulin Resistance and Atherosclerosis 297mentioning
confidence: 99%
“…Several studies found that the inverse correlation of CA-IMT with insulin resistance was no longer significant after adjustment for established risk factors in multivariate analysis in studies using the index of fasting proinsulin (12), HOMA-IR (15), KITT (14), FSIVGTT (11), or euglycemic clamp (13) as indices. Recent studies failed to find significant associations of CA-IMT with insulin resistance assessed by HOMA-IR (16) or SSPG (17). To our knowledge, only two studies have found a lack of a significant association of FA-IMT with insulin resistance assessed by FSIVGTT (21) or euglycemic clamp (13) in healthy subjects, and there are no such findings for type 2 diabetes.…”
Section: Discussionmentioning
confidence: 77%
“…The study by Laakso et al was the first to show reduced insulin sensitivity by euglycemic hyperinsulinemic clamp in nonobese, nondiabetic subjects with asymptomatic atherosclerosis, along with increased intimal-medial thickness (IMT), compared with control subjects (6). Subsequent studies mainly in non-diabetic subjects including those with hypertension or angina demonstrated complex outcomes concerning the association of IMT of the carotid artery with insulin resistance; significant (7)(8)(9)(10), partially significant, that is, significant in univariate but not in multivariate analysis (11)(12)(13)(14)(15), or nonsignificant (16,17). In type 2 diabetic patients, two studies found an inverse association of IMT of carotid artery with insulin resistance (18,19), but another did not (20).…”
Section: Introductionmentioning
confidence: 99%